(untitled) (Journal of Bangladesh Institute of Planners, 2023)
A global and comprehensive vision for a sustainable future is embodied in the UN Sustainable Development Goals (SDGs). Bangladesh began the implementation of SDGs from the beginning by including them in the national development plan. The obstacles and difficulties this country faces, have hindered its progress toward SDGs. Sector-based plans have emerged, and those approaches have created opportunities to reduce the difficulties related to the SDGs. The purpose of this paper is to explore the challenges, opportunities, and strategies related to Bangladesh’s SDGs across several fields. This research follows the systematic literature review process through the PRISMA tool for selecting the best-fit articles for meta-analysis. Meta-analysis helped determine the lagging goals and identify the underperforming sectors in the race to accomplish SDGs. The study finds out the progress of Bangladesh towards SDGs with the identification of the challenges besides analyzing the contribution of different sectors to implementing SDGs. According to the analysis, Bangladesh faces several challenges that affect all SDGs. The most prominent sectors for each research topic have been identified through qualitative data analysis with NVivo software. In achieving the SDGs, the institutional sector faces the most challenges, to overcome which it is also employing the most strategies. Along with achieving the SDGs, the opportunities that are being created in other sectors are also highlighted. This study reveals the problems and areas that require additional attention. JBIP, Vol. 16, 2023, pp. 77-104